(untitled) (The Pakistan Development Review, 2003)
The culturally, politically, and economically diversified regions in Asia are also different in terms of nutrition level. When under-nutrition is overcome by overnutrition, it leads to the incidence of diet-related diseases such as coronary heart disease, cancer, diabetes, hypertension, and stroke, etc. Some parts in Asia are undernourished and some are over-nourished, while a large number of countries are facing both these problems simultaneously. There are also instances of both under- and over-nourished people within the same household. This is what the authors call the double burden of malnutrition in Asia. This book deals with the magnitude, causes, consequences, and solutions to the problem of malnutrition. It is an excellent, comprehensive, and authoritative overview of the issues related to the direct and indirect policy interventions; capacity development, and resource allocation; and it is useful for the future course of action aimed at defeating the menace of malnutrition in the very diverse continent of Asia.